2002
DOI: 10.1046/j.1540-8175.2002.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Is It Open or Is It Closed? Thrombosis of a St. Jude's Tricuspid Valve Prosthesis

Abstract: A 49-year-old woman with mitral and tricuspid mechanical valve prostheses developed marked weight gain with increasing abdominal girth and facial plethora 4 weeks after anticoagulation was temporarily interrupted for abdominal surgery. Transthoracic and transesophageal echocardiography documented severe tricuspid stenosis and regurgitation. The two discs of the tricuspid prosthesis were immobilized, half open and half closed. The prosthesis was replaced and the patient did well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This finding stands in contrast to the atrial septal motion described in severe tricuspid regurgitation 1,2 in which there is systolic (and not diastolic) expansion of the right atrium secondary to systolic elevation of RA pressure (V‐wave). Prior case reports describe tricuspid stenosis complicating pacemaker‐related endocarditis as well as prosthetic valve thrombosis 3–6 . In one, the elevated right atrial pressure actually caused a paradoxical embolus through a patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding stands in contrast to the atrial septal motion described in severe tricuspid regurgitation 1,2 in which there is systolic (and not diastolic) expansion of the right atrium secondary to systolic elevation of RA pressure (V‐wave). Prior case reports describe tricuspid stenosis complicating pacemaker‐related endocarditis as well as prosthetic valve thrombosis 3–6 . In one, the elevated right atrial pressure actually caused a paradoxical embolus through a patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
“…Prior case reports describe tricuspid stenosis complicating pacemaker-related endocarditis as well as prosthetic valve thrombosis. [3][4][5][6] In one, the elevated right atrial pressure actually caused a paradoxical embolus through a patent foramen ovale. In our case, the elevated diastolic right atrial pressure was demonstrated by the bulging of the septum toward the left atrium in diastole as dictated by the diastolic RA-LA pressure gradient.…”
Section: Discussionmentioning
confidence: 99%